Trends of the use of pegylated granulopoiesis growth factors in clinical practice - single oncology centre experience since 2005 - Vokurka, S; Kliment, V; Kulhánková, J; Votavová, M; Janková, Z; Šorejs, O; Fiala, O; Fínek, J (Klinicka onkologie, 2024)
BACKGROUND: Pegylated granulopoesis growth factors (pegylated granulocyte colony-stimulating factors - PGCSF), pegfilgrastim and lipegfilgrastim, have established indications in the prophylaxis of febrile neutropenia (FN) after chemotherapy (CHT). Almost two decades after their introduction into practice, there is an opportunity to analyze their use development. PATIENTS AND METHODS: Retrospective and single centre analysis; patients with at least one and the first in their history application of PGCSF in 2005-2020 (N = 1,794); comparison of characteristics of the Historical group (2005-2010, N = 214) with the numerically comparable Recent group (2019, N = 222). RESULTS: In the period 2005-2020, there were 1 794 patients with at least one first application of PGCSF. Historical group vs. Recent: age 50 (18-77) vs. 58 (23-84) years; women 79 vs. 66%; breast and gastrointestinal cancer 67 and 3% vs. 29 and 25% respectively; primary FN prophylaxis 45 vs. 62%; CHT curative/neo-adjuvant 75 vs. 61%; CHT Q3W 94 vs. 53%; CHT Q2W 2 vs. 36%; CHT TAC/FEC/AC 57 vs. 25%; FOLFOX/FOLFIRI ± anti-VEGF/-EGFR 0.5 vs. 16% (all P < 0.05); FN incidence 4 vs. 0%; leukopenia as a separate reason leading to postponement of CHT despite prophylactic administration of PGCSF: 2.8 vs. 4.9%; musculoskeletal pain and arthralgia 9 vs. 5%; intolerance/allergy: 2 vs. 1 (all statistically n.s.). CONCLUSION: In 2019, compared to 2005-2010, we show an increase in the use of PGCSF with a shift to palliative CHT protocols and generally less risky for the development of FN. The efficacy and safety of PGCSF were consistent with the conclusions of published studies. More detailed analyses of indications for Q2W protocols, generally low-risk or infrequent non-standard situations can bring other important insights and are topics for ideally multicenter cooperation.
Keywords: dospělí; nádory; Chemotherapy-Induced Febrile Neutropenia; senioři nad 80 let; retrospektivní studie; Humans; lipegfilgrastim; lidé středního věku; Middle Aged; Aged, 80 and over; Young Adult; side effects; prevention; mladý dospělý; febrilní neutropenie vyvolaná chemoterapií; Polyethylene Glycols; faktor stimulující kolonie granulocytů; filgrastim; treatment; mužské pohlaví; Granulocyte Colony-Stimulating Factor; Adult; Adolescent; rekombinantní proteiny; polyethylenglykoly; ženské pohlaví; Recombinant Proteins; lidé; mladiství; Filgrastim; pegfilrastim; Neoplasms; Aged; Neutropenia; senioři; Retrospective Studies; Male; Female